Superior ankyloglossia syndrome - Tanvir Kabir Chowdhury; Mohammad Zonaid Chowdhury; Ayesha Sadia; Tanzil Farhad; Md Afruzul Alam (Elsevier, 2020)
We report a rare case of superior ankyloglossia syndrome in a male neonate who had palatoglossal adhesion, cleft palate, patent ductus arteriosus, penile chordee without hypospadias and penoscrotal transposition. He also had superior labial frenulum and posterior ankyloglossia. The mother had bad obstetric history, developed per vaginal bleeding during pregnancy and used progesterone. The palatoglossal adhesion was divided with bipolar diathermy under intravenous anaesthesia at 7th day of life and he awaits repair of other defects.